Needs Assessment of Gifted Education Programmes in Dubai; an investigative case study of governmental Primary Schools - ALGHAWI, MARIAM ALI (2016)
Gifted education, defined as the schooling of students demonstrating an exceptional ability to learn, is relatively new in the education system of the United Arab Emirates (UAE); hence, research on gifted education in the UAE is limited. This study was the first to investigate the implementation of gifted education programmes at seven primary government schools in Dubai. The main research question of the study was: What programs are offered for gifted learners in primary government schools in Dubai? And what is needed in order to improve the provisions of gifted education? The study adopted the National Association for Gifted Children (NAGC) gifted program standards as a framework. A sequential exploratory mixed-methods research design was employed with a triangulation of data to test the validity of the findings. The methods used to collect the data included classroom observations, interviews and a questionnaire survey with teachers, a focus group with parents, and a review of official documents. The conclusions were that although the provision of education for gifted students has progressed in Dubai in the last ten years, there is still room for improvement with regards to identification of gifted students and implementation of gifted policies and programs. School administrators and teachers need to better understand and implement the policies prescribed by the Ministry of Education. Based on the findings a set of recommendations is offered to better serve the gifted students of UAE in the future.